Analisis Koloni Bakteri pada Berbagai Sumber Air Minum - Irawati, Wahyu; Marcellie, Jessica; Suhartono, Andreas Valiant; Marvella, Eunike Bunga (Universitas Medan Area, 2023)
Drinking water is a fundamental necessity for human survival. In an era of advancing technology and busy lifestyles, bottled water, refillable water, and the use of water dispensers have become convenient choices. However, safe drinking water must be free from bacterial contaminants and chemicals. This research aims to analyze bacterial colonies from various sources of drinking water, such as bottled gallon water, hot water dispensers, and coldwater dispensers. The research results reveal that cold water dispensers have the highest number of bacterial colonies, totaling 1702, while hot water dispensers and gallon water contain only 2 and 13 bacterial colonies, respectively. Characteristics of the bacterial colonies in all samples include a yellow color, irregular margins, round shape, flat surface, and a hazy optical appearance. Additionally, Gram staining results indicate that the majority of bacterial isolates are Gram-negative, accounting for 76.92%. Factors influencing bacterial growth in drinking water from dispensers include insufficient cleanliness and inadequate sterilization during the installation of gallon water on the dispenser.